Rab Ne Bana Di Jodi and A Little Things Called Love in Kristeva’s Intertextuality - Kudsiyah Kudsiyah; Lusia Kristiasih Dwi Purnomosasi (Universitas PGRI Madiun, 2017)
The aim of this research is analyzing the phenotext, the genotext and finding the reason the symbol of culture which significance in modern era. Theory of intertextuality and semiotic are displayed to help this research. Phenotext and genotex are the part of intertextuality used in this research. Phenotext is a pattern which can be linked to the communication from subject to addressee. To find the data the researcher needs to choose what kinds of utterances in verbal form from the scene of both movies. The utterances can be find how the main character (subject) is faced with their pairs (addressee). In genotext, genotext is in a text points out the transfer from drive energy (body movement) includes the intonation or rhythm. The researcher can find how the main character articulates the structure which correlates with the physic structure such as body movement that belongs to symbolization of feeling expression and act. The data is taken from the scenes of Rab Ne Bana Di Jodi and A Little Things Called Love movies. The instrument of data is documentation The results of the study; in phenotext there are some dialogues used by the main character in verbal form, in genotext there are some visuals formula romance of in expressing the feeling with physic structure of both movies, and symbol of culture used by the main characters becomes the way of western for changing the mindset of Asian to follow their culture.